Intellectual Property Rights, Human Capital and Innovation in Emerging and Developing Countries - Loukil, Kamilia (Journal of Social Economics Research, 2020)
The innovation literature suggests that the protection of Intellectual Property Rights (IPR) is a key determinant of innovation. Recent studies suggest that IPR protection stimulates innovation only under certain conditions. In this paper, we suppose that IPR have a positive impact on technological innovation only in countries with high levels of human capital. The objective of this study is to examine the relationship between intellectual property rights, human capital and technological innovation in the context of emerging and developing countries. To measure innovation, we use the number of patents granted to inventors in a country by the United States Patent and Trademark Office. IPR variable is the Ginarte and Park index, while the stock of human capital is measured by the percentage of the total enrollment among the school-aged population over 15 at the tertiary level. Panel Threshold Regression is applied to data of 46 developing countries for the period 1980-2009. The estimation results provide evidence for the existence of nonlinear relationship between intellectual property rights and innovation depending on human capital’s initial level.